Voluntarily wheel running protects doxorubicin-induced kidney injury by inhibiting oxidative stress through mitochondrial function - Xin Jiang; Zeyu Wang; Longyun Wang; Yuqi Wang; Lijing Zhao; Hongyu Jiang (PLoS ONE, 2025)
Background Doxorubicin (DOX) has a broad anticancer spectrum and precise anticancer effects, but its clinical application is limited by severe multiorgan toxicity, among which nephrotoxicity is one of the main adverse reactions. In this study, the protective effect of voluntary wheel running on nephrotoxicity induced by DOX was observed, and its mechanism was initially discussed. Methods Forty male C57BL/6 mice were randomly divided into a control group (CTR), a voluntary wheel running group (EX), a doxorubicin model group (DOX) and a doxorubicin combined with voluntary wheel running group (COM). After 2 weeks of exercise, the mice were sacrificed. Serum creatinine (CREA), urea nitrogen (BUN), uric acid (UA), carbon dioxide combining power (CO2-CP), renal tissue apoptosis, oxidative stress and mitochondrial function indicators were assessed. Results Compared with those in the DOX group, the concentrations of CREA, BUN and UA decreased, the number of TUNEL-positive cells in kidney tissue decreased, the expression of antiapoptotic proteins increased, and the expression of proapoptotic proteins decreased in the COM group. In addition, the COM can reduce the ROS and MDA contents in kidney tissue, reduce peroxide accumulation and alleviate mitochondrial respiratory chain damage caused by DOX. Conclusions Voluntary wheel running can improve the mitochondrial function of renal cells and reduce oxidative stress damage, thus playing a protective role against nephrotoxicity caused by DOX. This study provides a new way to reduce the adverse reactions to chemotherapy in combination with the application of chemical drugs.